The Influence Of Work Environment And Rewards On Turnover Intention With Job Satisfaction As An Intervening Variable At PT. LEN Industri (Persero) - Devinda Iswari, Zara; Ratna Komala Putri, Dr. (International Journal of Science, Technology & Management, 2025)
Effective human resource management is crucial to achieving organizational success, especially in the face of escalating competition. With the intervening variable, job satisfaction, this study aims to explore how the work environment and pay affect employees' inclinations to leave. A quantitative approach was used, taking turnover intention as the dependent variable and job satisfaction as the mediating factor, and work environment and rewards as the independent factors. PT LEN Industri's permanent employees (PKWTT) made up the study population, and 184 of them were selected through non-probability purposive sampling. The validity and reliability of the research instruments were assessed using SmartPLS 4.0, and the data were descriptively analyzed using a continuum line and validated using structural equation modeling (SEM). The results show that incentives and the work environment both greatly increase job satisfaction, which is crucial for reducing the desire to leave.